PENGETAHUAN, SIKAP DAN PERILAKU PENUNGGU PASIEN TENTANG KECUKUPAN ASUPAN MAKANAN RAWAT DI RSUP DR KARIADI - Nurrohmiati, Siti; Subagio, Hertanto Wahyu; Murbawani, Etisa Adi (Universitas Diponegoro, 2019)
Background: Malnutrition remains a health problem in either developed and developing countries, caused by a variety of individuals and factors related to the disease. Caretaker/family support to help patient's intake, the attitude of the team manager of the patient, the procedure of advance examination, is an important factor to improve inpatients intake. But the association of knowledge, attitudes, and behavior patient's caretaker to the adequacy of inpatients food intake not yet unknown.Methods: This research is association research, performed at the Rajawali ward at dr. Kariadi Hospital with a total sample of at least 50 people. The measurement of knowledge, attitudes, and behaviors of patient's caretaker use detailed questionnaire. The answer of the respondent's questionnaire or interview processed by computer software to know the depth and the association between the variables.Results: Most of the respondents are women and 1,5 times than men. The age of respondents mostly above 50 years old (32%). Most of them are primary school graduates (39,3%). 76% of Respondent's income are less than 2,3 million rupiah. 55,4% are married. The level of respondent's knowledge about patient's food intake shows a good level of knowledge. Respondent's attitude regarding patient's food intake shows positive attitude about nutrition and adequacy of patient's food intake. Respondent's behaviour regarding patient's food intake shows a good result.Conclusion: a good knowledge influence a positive attitude, a positive attitude related to the behavior to the adequacy of patient's food intake, while the level of knowledge was not significantly related to the behavior of the adequacy of patient's food intake.Keywords: knowledge, attitude, behavior, patient?s caretaker, food intake.